Application of Service Service Application System in the Regional Service Agency of Gresik Regency (Study of Structural Upgrade Services) - Khobiburrohma, Eviva Nur; Hijri, Yana Syafriyana; Hadi, Krishno (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
E-Government is a form of public service implementation based on the use of information and communication technology. One of the government agencies that utilizes the sophistication of technology and information in public services is the Regional Personnel Agency of Gresik Regency. This government agency has an online system, namely "SAPK" which means the Personnel Service Application System. This application realizes the latest staffing data at every central and regional agency. This application is an application that is integrated into the center and each region has the authority to access. SAPK itself has many features in it, one of which is the promotion feature. The purpose of this research is to see the implementation of SAPK in promotion services. In addition, researchers also looked at what were the inhibiting factors in the implementation of SAPK. The type and approach of this research uses a descriptive qualitative approach. Sources of data obtained are primary data and secondary data with data collection techniques carried out namely interviews, observation and documentation. While the data analysis techniques carried out were data reduction, data collection, and drawing conclusions and verification. The results of the study are that the implementation of promotion services through SAPK at the Regional Personnel Agency of Gresik Regency uses Edward III's theory with 4 variables, namely communication, resources, disposition, and bureaucratic structure has been going well. The inhibiting factor experienced is that the SAPK application can only be accessed on certain servers and the connection is weak.